STRENGTH AND HIGH-PLASTICITY MATERIALS FRACTURE MECHANISMS UNDER DISCRETE WATER-DROPLET FLOW - Valery N. Varavka; Oleg V. Kudryakov (Advanced Engineering Research)
The field research results of the austenitic steel wear under the droplet impact erosion are presented. The stages of the erosive wear origin and development are considered. The leading part of the side cracks in the forming and growth of the erosion fracture craters, as specified in Marshall-Lawn model, is shown by the high-resolution scanning electron microscopy technique.